2015
DOI: 10.1088/0004-637x/802/1/53
|View full text |Cite
|
Sign up to set email alerts
|

Global Energetics of Solar Flares. Ii. Thermal Energies

Abstract: We present the second part of a project on the global energetics of solar flares and coronal mass ejections (CMEs) that includes about 400 M-and X-class flares observed with the Atmospheric Imaging Assembly (AIA) onboard the Solar Dynamics Observatory (SDO) during the first 3.5 years of its mission. In this Paper II we compute the differential emission measure (DEM) distribution functions and associated multi-thermal energies, using a spatially-synthesized Gaussian DEM forward-fitting method. The multi-thermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 40 publications
6
81
0
Order By: Relevance
“…Evidence for multithermal plasmas has been found by EUV and SXR spectroscopy (e.g., Dere & Cook 1979;McTiernan et al 1999;Chifor et al 2007) and by RHESSI HXR observations (Aschwanden 2007;Caspi & Lin 2010;Jain et al 2011). Recent studies using multiband EUV images from SDO/AIA Ryan et al 2014;Aschwanden et al 2015) and EUV spectra by SDO/EVE (Warren et al 2013;Kennedy et al 2013;Caspi et al 2014b) and by Hinode/EIS (Graham et al 2013) have finally provided well-constrained DEM distributions and have shown conclusively that the thermal component in solar flares is indeed multithermal in nature. The DEM distributions derived in these studies tend to be broad, and often a bimodal distribution is found, with a low-temperature peak at 1-2 MK (which is probably due to non-flaring foreground and background coronal material; cf.…”
Section: Evolutionary Effects and Multithermalitymentioning
confidence: 93%
“…Evidence for multithermal plasmas has been found by EUV and SXR spectroscopy (e.g., Dere & Cook 1979;McTiernan et al 1999;Chifor et al 2007) and by RHESSI HXR observations (Aschwanden 2007;Caspi & Lin 2010;Jain et al 2011). Recent studies using multiband EUV images from SDO/AIA Ryan et al 2014;Aschwanden et al 2015) and EUV spectra by SDO/EVE (Warren et al 2013;Kennedy et al 2013;Caspi et al 2014b) and by Hinode/EIS (Graham et al 2013) have finally provided well-constrained DEM distributions and have shown conclusively that the thermal component in solar flares is indeed multithermal in nature. The DEM distributions derived in these studies tend to be broad, and often a bimodal distribution is found, with a low-temperature peak at 1-2 MK (which is probably due to non-flaring foreground and background coronal material; cf.…”
Section: Evolutionary Effects and Multithermalitymentioning
confidence: 93%
“…We applied standard DEM-analysis (Aschwanden et al 2015) to estimate the radiation losses and the maximum thermal energy using the AIA observations. This analysis covers plasma , as in the work of Aschwanden et al (2015) for the flares.…”
Section: Goes Radmentioning
confidence: 99%
“…Such a configuration can be quantified by the differential emission measure (DEM), and recent EUV observations have confirmed that broad DEM distributions are common in solar flares (cf. Fletcher et al 2013;Graham et al 2013;Kennedy et al 2013;Warren et al 2013;Caspi et al 2014b;Ryan et al 2014;Aschwanden et al 2015).…”
Section: Nonisothermality Of the Thermal Plasmamentioning
confidence: 99%
“…Generally, the isothermal assumption will underestimate the thermal and radiative energies, in particular if a significant part of the DEM is outside the instrument temperature response. Recently, Aschwanden et al (2015) have derived the thermal energies for 400 M and X-class flares using DEMs derived from AIA multi-filter observations in the EUV. They found that using the isothermal assumption underestimates the thermal energy by a factor of ≈14 compared to the multithermal case.…”
Section: Nonisothermality Of the Thermal Plasmamentioning
confidence: 99%
See 1 more Smart Citation